From Data to Insights: An Analysis of Enrollment, Retention and Completion Rates at the Cagayan State University - Bravo, Edison Datul (International Journal of Learning and Development, 2024)
This study utilized the data visualization technique to explore the enrollment and graduation data of Cagayan State University- Carig Campus (CSU Carig). The study analyzed data for first-time full-time first year students entering the university from the first semester of school year 2018-2019 school year to the second semester of school year 2021-2022. The findings revealed that there were more female students enrolled in the eight colleges of the campus than male students, with the average ratio being 6:7. Most colleges had retention rates of 85% or greater, which was relatively high. However, the College of Veterinary Medicine had a retention rate of 72.47% in 2021–2022 which was substantially lower than that of the other colleges. The study also found that in terms of gender, the retention rates varied significantly across the colleges. The College of Industrial Technology has the largest male to female ratio, which may indicate that the technical and blue collar-related nature of the degrees it offers may draw a greater share of male students. On the other hand, the College of Arts and Sciences has the lowest male to female ratio, which suggests that women are more likely to pursue careers in the humanities, social sciences, and the arts. The retention rate for male students at the College of Engineering and Architecture was 62.13% in the academic year 2019–2020, but it significantly rose to 92.63% in 2020-2021 and 88.45% in 2021-2022, while it remained consistently higher than 80% for female students throughout all three academic years. With 100% of students graduating in the academic year 2021–2022, the College of Medicine achieved the highest graduation rate. These findings provide useful insights for CSU Carig that can help them in their decision-making about academic programs, student support services, and overall institutional performance.